2019
DOI: 10.1101/802843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active zone compaction in presynaptic homeostatic potentiation

Abstract: 19 20 * Correspondence should be adressed to M.H. (heckmann@uni-wuerzburg.de) and 21 M.M.P. (mila.paul@uni-wuerzburg.de) 22molecular environment for fast and precise neurotransmitter release (Kittel et al., 2006; 75 Held and Kaeser, 2018). Whereas the Brp N-term was mapped in membrane-76 proximity, its C-term covers an area of about 0.1 µm 2 , localizes about 155 nm above 77 the postsynaptic receptors (Fouquet et al., 2009; Liu et al., 2011) and is important for 78 tethering of synaptic vesicles (Hallerman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Finally, given these reductions in the density and intensity of active zone components, the total intensity of both BRP and Cac sfGFP per hyper-innervated NMJ was not significantly different from wild type despite the increase in their total number ( Figure 3G ). These results parallel recent studies that have shown that while the number and intensity of individual active zones can vary at NMJs, the total abundance of active zone protein remains constant (Graf et al, 2009 ; Goel et al, 2019a , b ) or can reflect nanoscale remodeling of active zone components (Böhme et al, 2019 ; Mrestani et al, 2020 ). Together, hyper-innervated NMJs express a target-specific reduction in both the number and intensity of release sites per bouton and a parallel reduction in presynaptic release probability that stabilizes synaptic strength, while no reciprocal changes are observed at hypo-innervated counterparts.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, given these reductions in the density and intensity of active zone components, the total intensity of both BRP and Cac sfGFP per hyper-innervated NMJ was not significantly different from wild type despite the increase in their total number ( Figure 3G ). These results parallel recent studies that have shown that while the number and intensity of individual active zones can vary at NMJs, the total abundance of active zone protein remains constant (Graf et al, 2009 ; Goel et al, 2019a , b ) or can reflect nanoscale remodeling of active zone components (Böhme et al, 2019 ; Mrestani et al, 2020 ). Together, hyper-innervated NMJs express a target-specific reduction in both the number and intensity of release sites per bouton and a parallel reduction in presynaptic release probability that stabilizes synaptic strength, while no reciprocal changes are observed at hypo-innervated counterparts.…”
Section: Resultssupporting
confidence: 87%
“…Although a similar reduction in the abundance of active zone proteins at individual release sites has recently been found in mutations that cause synaptic overgrowth at the NMJ (Goel et al, 2019a , b ), the adaptations observed in the case of hyper-innervation are distinct in that they are: (1) target-specific; and (2) involve a reduction in active zone density in addition to their apparent intensity. Although increased fluorescence intensity is typically interpreted to reflect enhanced protein abundance, a recent study using Localization Microscopy showed that increased active zone intensity may instead reflect a more compact nanoscopic arrangement (Mrestani et al, 2020 ). Nonetheless, it is remarkable that both the number and intensity of active zone components can be selectively reduced and calibrated at hyper-innervated terminals without any apparent changes at adjacent terminals shared by the same neuron on the hypo-innervated target.…”
Section: Discussionmentioning
confidence: 99%
“…PhTx application at the Drosophila NMJ results in an increase in immunofluorescence intensity of several active-zone proteins, including the scaffolding protein Bruchpilot (Brp), suggesting increased Brp abundance and/or reorganization ( Böhme et al, 2019 ; Mrestani et al, 2021 ; Gratz et al., 2019 ; Weyhersmüller et al., 2011 ). We therefore examined whether Gyki-induced PHP also involves Brp modulation.…”
Section: Resultsmentioning
confidence: 99%
“…Developmental studies of the NMJ using ExM imaging show a progressive increase in BRP area and complexity as the synapse matures (Jiang et al, 2018; Figure 5D). STED and STORM have further characterized the rapid remodeling of BRP and other active zone components during synaptic plasticity, showing that the presynaptic proteins regulating transmission are modulated to maintain synaptic efficacy during homeostatic scaling (Weyhersmüller et al, 2011;Böhme et al, 2019;Mrestani et al, 2019). STORM imaging of the NMJ has further resolved individual BRP clusters within rings at the active zone (Ehmann et al, 2014) and was later used to discover species differences in subsynaptic NMJ active zone organization in mouse vs. humans (Jones et al, 2017).…”
Section: Super-resolution Imaging Of Neural Development and Plasticitmentioning
confidence: 99%